2019
DOI: 10.1186/s13690-019-0352-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of unconditional child cash grant on child malnutrition and its immediate and underlying causes in five districts of the Karnali Zone, Nepal – A trend analysis

Abstract: Background The impact of unconditional cash transfers on child malnutrition and its determinants remains poorly understood. The aim of this study was evaluate the impact of an unconditional child cash grant on children’s nutritional status and its immediate (infant and young child feeding, dietary diversity, food consumption, and child infection and care) and underlying (household food security; Water, Hygiene and Sanitation (WASH) determinants among children younger than five years in the Karnali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
5
16
1
Order By: Relevance
“…[32,33] Also aligned with previous research, reductions in food insecurity after receipt of cash were found [34], which in some development schemes have resulted in further reductions in malnutrition and other related outcomes. [35] These spending habits were consistent with the primary intention of shortterm emergency cash assistance programming in helping households meet their basic needs. The present study did not capture these nutrition-related outcomes, thus, it remains unclear whether increased food security could improve potential malnutrition outcomes within more fragile settings, as recent studies from Somalia internally displaced persons camps and in Niger found improvements in food security, but no change in malnutrition amongst young children.…”
Section: Discussionsupporting
confidence: 57%
“…[32,33] Also aligned with previous research, reductions in food insecurity after receipt of cash were found [34], which in some development schemes have resulted in further reductions in malnutrition and other related outcomes. [35] These spending habits were consistent with the primary intention of shortterm emergency cash assistance programming in helping households meet their basic needs. The present study did not capture these nutrition-related outcomes, thus, it remains unclear whether increased food security could improve potential malnutrition outcomes within more fragile settings, as recent studies from Somalia internally displaced persons camps and in Niger found improvements in food security, but no change in malnutrition amongst young children.…”
Section: Discussionsupporting
confidence: 57%
“…In India (Corsi, Mejía-Guevara, & Subramanian, 2016) and across South Asia (Kim, Mejía-Guevara, Corsi, Aguayo, & Subramanian, 2017), past and present socioeconomic conditions were found to be the strongest predictors of child undernutrition out of a comprehensive set of other known risk factors including those related to environmental and household practices. Household wealth directly affects one's ability to consistently secure food and access proper sanitation and health services, thereby increasing the risk of poor nutrition outcomes in children (Renzaho et al, 2019). Thus, it is important to monitor child malnutrition indicators across different levels of household wealth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the few studies available have analyzed cash transfers targeting several outcomes (e.g. education and health) and not specifically paid maternity leave, in spite that some of these studies have shown that cash transfer may have positive impact on breastfeeding outcomes [39][40][41][42][43][44]. This study is the first to provide such cost estimates for Indonesia, and as such can provide urgently needed evidence for policy making purposes in the context of supporting recommended breastfeeding practices, especially given the relatively low health budget in Indonesia (under 5% share of GDP as of 2014) [45].…”
Section: Introductionmentioning
confidence: 99%